PENGARUH LINGKUNGAN KERJA, EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI DAN KENYAMANAN FISIK TERHADAP KINERJA KARYAWAN PADA LEMBAGA PERKREDITAN DESA SE – KECAMATAN SUKAWATI - Febriari Ni Putu Pande; Ayu Putu Cita (Hita Akuntansi dan Keuangan, 2022)
Employee performance is very influential on the progress of an institution, especially in bank and non-bank financial institutions such as Village Credit Institutions that aim to uncover and present the fact that employee performance is very influential on the progress of a Sukawati District Village Credit Institution such as the work environment, the effectiveness of SIA use, and physical comfort. This research focuses on village credit institutions in Sukawati subdistrict. This study was conducted in 33 LPD in Sukawati District with 280 people. The sampling method used is a non probability sampling method with purposive sampling technique with certain considerations. The sample was taken from a total of 99 related to SIA, namely the head of LPD, treasurer and business administration. Data collection is carried out with penyebaran questionnaire and interviewin LPD Sukawati Subdistrict with the necessary data analysis, namely multiple linear analysis. This research provides results of the work environment, the effectiveness of the use of Accounting Information System and physical comfort positively affect the performance of LPD employees of Sukawati Subdistrict, so it is strongly supported by TAM theory and TPC Theory.